Employee Performance in Population Services Quality Timeliness and Technology Use - Aviyah, Aviyah; Mursyidah, Lailul (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Employee performance in public administration is crucial for service quality. Specific Background: This study examines employee performance in population administration services at Kupang Village, Jabon District, Sidoarjo Regency, focusing on community needs and technological adaptation. Knowledge Gap: While prior research has addressed public service performance, gaps exist regarding specific performance indicators in local contexts. Aims: This study aims to analyze performance using five indicators: Work Quality, Timeliness, Initiative, Ability, and Communication. Results: Findings show optimal work quality and initiative, yet timeliness and ability are partially lacking due to attendance issues and varying technological skills. Novelty: This research highlights the interplay between employee competencies and community demographics. Implications: Enhancing training in technology and establishing clear protocols could significantly improve service delivery and community satisfaction, fostering better governance and public trust. Highlights: Optimal Work Quality: Employees demonstrate high-quality service through detailed work and effective communication with the community. Need for Timeliness: Issues with employee punctuality impact overall service delivery and community satisfaction. Technological Competency: Varying levels of technology use among employees highlight the need for targeted training and support. Keywords: Employee Performance, Service Quality, Community Needs, Population Administration